The Influence of Social Security for Workers, Length of Service, and Incentives on the Work Productivity of Employees at Pawnshops in Mataram City - Aziza Catya Wardhani; St. Maryam; Sataruddin Sataruddin (Indonesian Development Economics and Localities, 2025)
Financial institutions, both banks and non-banks, play an important role in supporting economic activities. Over time, the distribution of funds by non-bank financial institutions for working capital, consumption, and investment has increased, indicating that both are actively contributing to meeting the needs of the community. This study aims to analyze the influence of social security for workers, length of service, and incentives that have a significant effect on the work productivity of Pegadaian office employees in Mataram City. The type of research used is quantitative descriptive research with the analysis technique used is multiple linear regression analysis with the Eviews 12 application. After testing was carried out, the results obtained partially were that social security for workers had a positive and insignificant effect on employee work productivity while length of service and incentives had a positive and significant effect on employee work productivity. Simultaneously, the three variables have a positive and significant effect on the work productivity of Pegadaian office employees in Mataram City.